2020
DOI: 10.1109/access.2020.3024890
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive GNSS Receiver Design for Highly Dynamic Multipath Environments

Abstract: Ubiquitous navigation requires timely, uninterrupted and accurate estimate of receiver's position at all times, in all environments and for all modes of transportation and it is highly dependent on satellite availability, geometry and accurate positioning estimation. However, the availability, continuity and accuracy of a GNSS can be severely affected in a highly dynamic environment due to blockage, fading and multipath. This results in positioning information inaccurate, unreliable and sometimes unavailable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Lastly, Legendre sequence-based codes show excellent correlation characteristics, and they have recently been used in GPS L1C and BDS B1C signals. As the fields of the application of the GNSS have expanded along with the recent development of the industries, studies to provide high precision and additional functions of GNSS receivers have been extensively conducted [8][9][10][11][12][13][14][15][16][17]. In addition to the simple role of receiving signals and performing navigation calculations, advanced signal technologies, such as anti-jamming [8] and anti-spoofing [9], are applied, and studies on multiconstellation and multi-frequency receivers [10][11][12] are being conducted for high-precision high-reliability location calculations.…”
Section: ]mentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, Legendre sequence-based codes show excellent correlation characteristics, and they have recently been used in GPS L1C and BDS B1C signals. As the fields of the application of the GNSS have expanded along with the recent development of the industries, studies to provide high precision and additional functions of GNSS receivers have been extensively conducted [8][9][10][11][12][13][14][15][16][17]. In addition to the simple role of receiving signals and performing navigation calculations, advanced signal technologies, such as anti-jamming [8] and anti-spoofing [9], are applied, and studies on multiconstellation and multi-frequency receivers [10][11][12] are being conducted for high-precision high-reliability location calculations.…”
Section: ]mentioning
confidence: 99%
“…As the fields of the application of the GNSS have expanded along with the recent development of the industries, studies to provide high precision and additional functions of GNSS receivers have been extensively conducted [8][9][10][11][12][13][14][15][16][17]. In addition to the simple role of receiving signals and performing navigation calculations, advanced signal technologies, such as anti-jamming [8] and anti-spoofing [9], are applied, and studies on multiconstellation and multi-frequency receivers [10][11][12] are being conducted for high-precision high-reliability location calculations. Especially, studies on single code generators that support various codes are actively conducted for the implementation of multi-constellation and multi-frequency receivers so that single receivers can support multiple codes [13][14][15][16][17].…”
Section: ]mentioning
confidence: 99%
See 2 more Smart Citations
“…An additional experimental setup for hemispheric photography was made at different altitudes to investigate if a correlation exists between GNSS performance and geometric blockage, or the sky openness ratio (SOR), independent from the multipath error in urban airspace. While previous studies have demonstrated a relationship between the visible sky (blockage factor) and positional accuracy, the contribution by the sky openness ratio was not isolated [ 6 ]. While no formal correlation had been specified, the building geometries and their blockage of visible sky were included as a parameter in the evaluation of GNSS performance in urban environments, as specified by the European Telecommunications Standards Institute (ETSI) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%